Effect of compactive effort on the performance of fine-grained soil–cement mixtures. Issue 3 (30th August 2019) - Ali, Ammar; Cortes, Douglas D.; Weldon, Brad; Bandini, Paola; Lommler, John C.
Abstract : Cement stabilisation is a common chemical ground improvement technique. However, the energy-intensive production of Portland cement and its associated high carbon dioxide emissions give soil–cement mixtures a low sustainability rating. Cement treatment of fine-grained soils is particularly problematic due to the relatively high cement contents used in practice (i.e. >12% by mass). Decreasing the amount of cement necessary to ensure appropriate mechanical performance in roadway subgrades, particularly fine-grained subgrades, could rapidly enhance the sustainability rating of cement stabilisation. This work explored the behaviour of low- and high-plasticity clays treated with low cement contents (3–6% by mass). In this experimental study, the small- and large-strain mechanical responses of the materials were evaluated using P-wave velocity and unconfined compression tests, respectively. The results indicate that the small-strain stiffness and strength of soil–cement mixtures is very sensitive to changes in compaction water content and compactive effort. The authors conclude that while the practical application of low-cement–soil mixtures is possible, it requires strict construction control and adherence to very tight tolerances, which makes it impractical for most highway construction projects.